2017
DOI: 10.1177/1744259117697389
|View full text |Cite
|
Sign up to set email alerts
|

An analytical approach to assess the influence of the massive wall material, thickness and ventilation system on the Trombe wall thermal performance

Abstract: The influence of the massive wall material, thickness and ventilation system on the Trombe wall thermal performance was analysed based on an analytical methodology. Results obtained from experimental work will also be added to this study. During the heating season, for the non-ventilated Trombe wall, the global heat gains decrease is not proportional to the thickness increase, and this ratio depends on the massive wall material heat storage capacity. A ventilation system in the massive wall leads to higher hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It was noticed that a certain thermal inertia in the slab provides better indoor comfort in both summer and winter. Briga Sá et al [14] described the influence of the massive wall material, thickness and ventilation system on the Trombe wall thermal performance. It has been demonstrated that during the heating season, for the nonventilated Trombe wall, the global heat gains decrease is not proportional to the thickness increase.…”
Section: Introductionmentioning
confidence: 99%
“…It was noticed that a certain thermal inertia in the slab provides better indoor comfort in both summer and winter. Briga Sá et al [14] described the influence of the massive wall material, thickness and ventilation system on the Trombe wall thermal performance. It has been demonstrated that during the heating season, for the nonventilated Trombe wall, the global heat gains decrease is not proportional to the thickness increase.…”
Section: Introductionmentioning
confidence: 99%
“…Renewable energy resources have been employed in buildings with many methods [1], and among them, solar radiation has been harnessed for natural ventilation with solar chimneys [2]- [5]. A typical solar chimney consists of an air channel enclosed by a transparent cover and an absorber surface, such as a building wall [6]- [10]. Once exposed to solar radiation, the transparent cover allows the radiation to pass through and absorb the absorber surface.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, an increase in the internal temperature of 61% was obtained. In the absence of an occlusive device, the temperatures of the outer surface of the massive wall exceeded 60 °C, and when it was installed, they decreased to 30 °C or below (Briga Sá et al, 2018). Using the life cycle cost (LCC) method, the optimal ratio of the Trombe wall area from a thermal and economic point of view is 37%.…”
mentioning
confidence: 99%